Evaluation of Novel Resveratrol Conjugate and Nanoparticle Formulations for Enhanced Anticancer Activity - Yee, Yan Jing (Curtin University, 2018)
Resveratrol is known to undergo rapid metabolism and degradation in vivo. The aim of this project is to synthesise polymeric resveratrol conjugates for formulation into nanoparticles for enhanced anticancer treatment by decreasing the metabolism and degradation rate of resveratrol in vivo. Conjugated resveratrol nanoparticles were found to suppress tumour growth in vivo in a melanoma mouse model although in vitro data shows lesser anti-proliferative effect than resveratrol alone.